Casa de ferreiro, espeto de pau: uma análise das relações retóricas a partir do uso dos provérbios como estratégia argumentativa em textos da internet - Ana Clara Gonçalves Alves de Meira (2015)
In this study, we analyzed the usage of proverbs with no verbal nucleus and no connectors within texts extracted from the internet, whether their occurrences happen on their titles or on the body text, aiming at investigating the role of rhetorical relations in textual coherence and organization. To achieve that objective we based upon the Functionalist Approach focusing on the North American West Coast Functionalism in order to demonstrate the importance of a language study that is not restricted to seeing language as form but that also takes function under consideration. Within that theoretical referential we elected Rhetorical Structure Theory RST, which studies the implicit relations that exist between parts of a text and how they are connected to textual coherence. Since this work also verified the way the metaphorical process contributes to either reassuring or justifying a chosen emerging rhetorical relation at a specific proverb, we indicated which theoretical perspective was considered when analyzing the metaphor during this research. The corpus comprised 10 proverbs, extracted from texts from the internet using Google search engine, which were analyzed in 20 different texts. In this respect, we investigated the occurrence of a same proverb in two different texts to observe the role of a particular communicative situation in creating semantic relations. Our hypothesis was that the existing generic and specific information in the proverbs could contribute to justifying that analyzing specific rhetorical relations was plausible. Furthermore, another hypothesis was that a particular situation could have influence on the rhetorical relation established in a certain proverb. The results demonstrated that the existing generic and specific information in the proverbs contributed to reassure a relation defined as plausible to a specific proverb. We also observed that even in diverse particular situations the rhetorical relation of a same proverb was not modified in most cases. Nevertheless, such result did not invalidate the proposed hypothesis inasmuch as although a proverb could present the same rhetorical relation in diverse specific situations, the particular situations contributed to somehow building new meanings to the proverbs analyzed. We consider that studying existing implicit relations in proverbs from texts extracted from the internet can collaborate with a study that is not restricted to seeing language as form but benefits syntactic, semantic and pragmatic aspects without disregarding social and cultural factors.